2014
DOI: 10.1186/s13014-014-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial high-dose rate brachytherapy as boost for anal canal cancer

Abstract: AimTo assess clinical outcomes of patients treated with a high-dose rate brachytherapy boost for anal canal cancer (ACC).MethodsFrom August 2005 to February 2013, 28 patients presenting an ACC treated by split-course external beam radiotherapy (EBRT) and HDR brachytherapy with or without chemotherapy in a French regional cancer center in Nice were retrospectively analyzed.ResultsMedian age was 60.6 years [34 – 83], 25 patients presented a squamous cell carcinoma and 3 an adenocarcinoma; 21 received chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…In our analysis, we chose a relatively high threshold of 40 patients in order to analyze only numerically representative series and therefore, with more reliable results due to higher statistical homogeneity. However, some interesting series [ 33 , 34 , 35 ] with smaller sample size (< 40 patients receiving BRT boost) have been published in the last decades. Saarilahti et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we chose a relatively high threshold of 40 patients in order to analyze only numerically representative series and therefore, with more reliable results due to higher statistical homogeneity. However, some interesting series [ 33 , 34 , 35 ] with smaller sample size (< 40 patients receiving BRT boost) have been published in the last decades. Saarilahti et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, particularly with IMRT technique, we delivered a higher EBRT dose compared to other BT boost experiences published. Moreover, other authors reported a protocol that established BT after 4-6 weeks [ 18 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another analysis published in the same year by Falk et al . [ 18 ], these parameters were 0.58 and 0.38, respectively. Major et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fistulae including recto-vaginal, rectovesical, anal, or rectal fistula occur in 0.7-22.2% of patients [75,105,[108][109][110][111][112]. Other reported adverse symptoms included perineal/anal/rectal pain, necrosis, colonic obstruction, small bowel obstruction, perforation, telangiectasia, constipation, abdominal pain, tenesmus, enteritis, rectal mucus, and perianal numbness [36,66,84,107,[113][114][115][116][117][118].…”
Section: Other Gi Toxicitiesmentioning
confidence: 99%